Diseño de un sistema de bombeo para un almacenamiento de agua de riego en los sectores de Chanchico y Tiobamba de la parroquia Eloy Alfaro, cantón Latacunga, Provincia de Cotopaxi - Gualancañay Miñarcaja, Darwin Patricio (2017)
The provision of water for living beings in many cases requires the implementation of pumping and storage systems as well as their transportation and distribution, which demand energy for their operation; The objective of this researching is to design a pumping system for the irrigation system "NUEVA VIDA", the main source of this water resource comes from a natural water slope, which constitutes the union of the rivers ISINCHE and QUEVEDOS PATOA which is a vital source for all sectors where it travels these rivers. The implementation of this pumping system will allow the continuous supply of the water resource to the sector. This study uses the scientific and experimental methods, which begins with the documentary study, presenting various experiences of applications, techniques of design and construction of pump systems in rural sectors, to improve agricultural and cattle production. In addition, an experimental work is carried out by means of a pumping system, with the purpose of supplying a flow of 75 m3/h required for the production in the sector where it is at a height of 129 m to a length of 450 m, above the source of water. The economic evaluation based on the implementation of the proposal indicates that the investment is recoverable in 9 years, considering a current interest rate of 16.06% currently in the local bank, and is an alternative of social assistance and care environment.